Special Judo Fitness Test and biomechanics measurements as a way to control of physical fitness in young judoists - Boguszewska, K.; Boguszewski, D.; Busko, K. (Archives of Budo, 2010)
Background and study aim: The aim of this study was to compare biomechanics and special methods control of judo training process. Material and methods: The study was conducted on eight junior judoists. Special abilities was evaluated using a Special Judo Fitness Test (SJFT). Muscle torque measurements in static conditions were performed. Ten muscle groups were examined: flexors and extensors of the trunk, shoulder, elbow, hip and knee. The maximal power and height of jump were measured at BCMJ and CMJ jumps. Power-velocity relations were determined from 5 maximal cycle ergometer exercise bouts at increasing external loads equal to 2.5, 5.0, 7.5, 10.0 and 12.5% of body weight. Results: Mean values (±SD) index of Special Judo Fitness Test was 12.71±1.94. The values of BCMJ relative maximal power and height of jump were 44.75±8.97 W•kg-1 and 0.526±0.071 m, respectively. The mean values of Pmax 900.8±152.9 W and Pmax/mass 13.44±1.28 W•kg-1 were corresponding to mean optimal velocity 119.3?16.0 rpm. The relative values of the muscle torque were correlated with index of SJFT, the coefficients ranging from -0.15 to -0.68. Index of SJFT correlated significantly with BCMJ values of the relative power and height of jump (r = -0.72 and -0.88, respectively). SJFT index correlated with power output and velocity in the maximal cycloergometer test, the coefficients ranging from -0.71 to 0.48. Conclusion: In training process should be used biomechanics measurements, physical fitness tests and special fitness tests characteristic for own discipline as well. It will give optimal training control.